HUBUNGAN EFIKASI DIRI DAN REGULASI DIRI TERHADAP TANGGUNG JAWAB BELAJAR SISWA KELAS IV DI SD GUGUS GATOTKACA - Oktaviana Annisa Zahra; Ika Oktavianti; F Shoufika Hilyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The lack of student responsibility for their learning responsibilities is caused by factors that exist in students, namely the lack of student confidence in the abilities they have and the lack of student ability to regulate or control the emotions that exist in students during learning, especially in science subjects. The purpose of this study was to determine whether there was a positive and significant relationship of student efficacy and self-regulation on the learning responsibilities of grade IV students in science subjects. The method used is a quantitative research method using a correlation approach to analyze the relationship between variables. The data analysis techniques used are descriptive statistics and regression analysis using SPSS software. The sample of this study consisted of 62 students in grade IV of SD Negeri Surjo 01 and SD Negeri Surjo 02. The results of this study include: 1. The relationship between Self-Efficacy and Student Learning Responsibility obtained a result of 0.615 p < 0.001 or 61.5% and was in the positive and significant category, 2. The relationship between Self-Regulation and Student Learning Responsibility obtained a result of 0.623 p < 0.001 or 62.3% and was in the positive and significant category, 3. The relationship between Efficacy and Self-Regulation and Student Learning Responsibility together obtained an R Square Change result of 0.583 or 58.3% and was in the positive and significant category. Thus, these findings show that both self-efficacy and self-regulation or self-efficacy and self-regulation together have a positive and significant relationship in each variable.